PENGARUH PENERAPAN TEKNIK CAWAN IKAN (FISH BOWL TECNIQUE) DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 5 AWAHLUNTO - Linda, Eva; Rismen, Sefna; Lovia, Lita (Pendidikan Matematika, 2013)
This research is motivated by the lack of understanding of mathematical concepts class VIII SMPN5 Sawahlunto . This is due to learning is centered on the teachers and students are less active in the learning of mathematics . This study aimed to determine the effect of the application of fish dishes accompanied quiz better than students understanding of mathematical concepts by applying conventional learning in class VIII SMPN5 Sawahlunto and to find out how the development of students understanding of mathematical concepts by applying techniques of fish dishes accompanied quiz grade students in mathematics learning SMP N 5 VIII Sawahlunto.This type of research is experimental research design randomized trials on the subject . Is a class VIII student population SMP N 5 Sawahlunto . Sampling technique is random , class is class VIII1 chosen as the experimental class and the control class VIII4 class . Research instrument in the form of quizzes and final test , which tests understanding of mathematical concepts which consists of 5 items in the form of essays, with a reliability of 0.8545 means that about reliable . Based on the analysis of the data found that the two classes are normally distributed and homogeneous samples at significance level Î± = 0.05 . Hypothesis test results obtained P - value = 0.011 is less than Î± = 0.05 . So it is concluded that the students understanding of mathematical concepts by applying techniques of fish dishes accompanied quiz better than students understanding of mathematical concepts with conventional learning in class VIII SMPN5 Sawahlunto .